Project-based learning in Media Learning Material Development for Early Childhood Education - Hayati, Miratul; Syaikhu, Ahmad (Al-Athfal: Jurnal Pendidikan Anak, 2020)
This study aims to create and develop teaching materials for early childhood education (PAUD) media units to facilitate learning processes. The teaching materials developed are compiled with a project-based learning approach. The research was conducted on the PAUD media unit in the Early Childhood Islamic Education (PIAUD) undergraduate program at UIN Syarif Hidayatullah Jakarta. This research is following Dick and Carey’s model of Research and Development. The development stage focuses on determining instructional goals, analyzing learning materials, analyzing student abilities in the learning context, determining learning targets, developing instruments, developing project-based learning strategies, and applying them to learning. The results showed that students could develop media in line with learning needs and aspects of children’s development using teaching materials.